Application and Multidisciplinary Aspects of Wireless Sensor Networks Concepts, Integration, and Case Studies - Gavrilovska, Liljana; Krco, Srdjan; Milutinovic, Veljko; Stojmenovic, Ivan.; Trobec, Roman; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2011)
It is a general trend in computing that computers are becoming ever smaller and more interconnected, and sensor networks - large networks of small, simple devices - represent a logical extreme of this trend. Wireless sensor networks (WSNs) are attracting an increasing degree of research interest, with a growing number of industrial applications starting to emerge. Two of these applications, personal health monitoring and emergency/disaster recovery, are the focus of the European Commission project ProSense: Promote, Mobilize, Reinforce and Integrate Wireless Sensor Networking Research and Researchers. This hands-on, useful introduction to WSN systems development presents broad coverage of topics in the field, contributed by researchers involved in the ProSense project. It emphasises the practical knowledge required for the successful implementation of WSNs. The first part of the work covers basic issues of sensors, software, and position-based routing protocols. Part Two focuses on multidisciplinary issues, including sensor network integration, mobility aspects, geo-routing, medical applications, and vehicular sensor networks. The remaining two parts present case studies and further applications. Topics and features: Begins with a Foreword by the Nobel Laurate Professor Martin Perl, of Stanford University Presents a broad overview of WSN technology, including an introduction to sensor and sensing technologies Investigates real-world applications of WSN systems in medical and vehicular sensor networks Contains an extensive section on case studies, providing details of the development of a number of WSN applications Discusses frameworks for WSN systems integration, through which WSN technology will become fundamental to the Future Internet concept Providing holistic coverage of WSN technology, this text/reference will help graduate students of computer science, electrical engineering and telecommunications toward mastering the specific domains of this emerging area. The book will also be a valuable resource for researchers and practitioners interested in entering or exploring the field. Dr. Liljana Gavrilovska is a professor at the Faculty of Electrical Engineering and Information Technologies of the Ss. Cyril and Methodius University in Skopje, Macedonia. Dr. Srdjan Krco is a senior researcher at the Ericsson Ireland Research Centre. Dr. Veljko M. Milutinovic, FIEEE, is a professor at the Department of Computer Engineering of the University of Belgrade, Serbia. Dr. Ivan Stojmenovic is a professor at the School of Information Technology and Engineering of the University of Ottawa, Canada. Dr. Roman Trobec is an associate professor at the Department of Communication Systems of the Jožef Stefan Institute, Slovenia.
Intoduction: A Bird s Eye View of Wireless Sensor Networks -- PART I: BASIC ISSUES -- Sensors -- Software Issues -- Position-Based Routing Protocols -- PART II: MULTIDISCIPLINARY ISSUES -- Sensor Networks Integration -- Mobility Aspects in WSN -- Modelling for Georouting in Multihop Wireless Networks -- Medical Applications of WSNs -- Optimized Placing of ECG Electrodes in WSN Applications -- Vehicular Sensor Networks: General Aspects and Implementation Issues -- PART III: CASE STUDIES -- FEEIT WSN Testbed: Effective System for Providing Emergency Situations Prevention and Surveillance -- ETF WSN Testbed: Practical Health Enhancing Application of WSNs -- PART IV: BIRDS OF A FEATHER -- Ubiquitous Sensor Networks -- eMuseum -- The PAR Logistics Solver Problem.
Keywords: Computer science; Computer Communication Networks; Computer Science; Computer Communication Networks